The secret river - Rawlings, Marjorie Kinnan, 1896-1953.; Dillon, Leo; Dillon, Diane (New York : Atheneum Books for Young Readers, 2009)
Young Calpurnia takes her dog, Buggy-horse, and follows her nose to a secret river in a Florida forest, where she catches enough fresh fish to feed her hungry neighbors, even after giving some to the forest creatures she meets on the way home.
Keywords: Fishing -- Fiction; Hunger -- Fiction; Forests and forestry -- Fiction; Dogs -- Fiction; Forest animals -- Fiction; Florida -- Fiction